Global and Local Dynamics in Film Collaboration and Production - Timothy Ekeledirichukwu Onyejelem (Budapest International Research and Critics University, 2026)
The globalization of film production has intensified cross-border collaborations, reshaping creative practices, industrial structures, and cultural representations within national cinema industries. This paper examines the global-local dynamics that underpin film collaborations between Nollywood filmmakers and their counterparts in Hollywood and Bollywood. Based on the theoretical postulation of Diffusion of Innovation, the paper interrogates how power relations, market access, technological exchange, and cultural identity are negotiated within these transnational partnerships. It argues that while such collaborations offer Nollywood opportunities for skills transfer, international visibility, and market expansion, they also reproduce asymmetrical power structures that privilege dominant global film industries. The study further explores how local narratives, aesthetics, and production practices are reconfigured to meet global market expectations, often resulting in hybridized cinematic forms. The paper concludes that global and local dynamics in film collaboration and production reveal the complex negotiations that shape contemporary transnational cinema. Nollywood’s collaborations with Hollywood and Bollywood demonstrate how global partnerships can simultaneously function as sites of opportunity and constraint, facilitating access to capital, technology, professional networks, and international markets, while also embedding unequal power relations that influence creative control, narrative framing, and cultural representation.